Anti-Racism Representation in Song on Ecrit Les Murs (Van Dijk Frame) - Simorangkir, Imelda Malawaty; Sofiani, Yulia (Journal of Community Research and Service, 2023)
This research uses French songs. The song is called On écrit sur les murs. This song is sung by Kids United, which is a children's singing group, consisting of six people. This arts group is a group formed by UNICEF. The researchers used van Dijk's critical discourse theory, which is used to dissect the meaning in the lyrics of the song On écrit sur les murs  Therefore, the purpose of this reseacrh is to find the meaning of the description of the macro-micro thematic system, proposed by van Dijk This research used a descriptive qualitative method. The research techniques in this research were listening, translating and analyzing song lyrics. The result of the research is that this song conveys anti-racism. They poured their feelings on a wall. Walls are used as a circle image, because many children everywhere often write on walls, especially walls on main roads to express their aspirations.